1990
DOI: 10.1073/pnas.87.15.5998
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a nucleotide exchange-promoting activity for p21ras.

Abstract: The biological activity of proteins encoded by the ras family of oncogenes is dependent on whether they are bound to GTP or GDP: the type of nucleotide bound is dependent on the rate of GTP hydrolysis (promoted by the GTPase-activating protein, GAP) and the rate of nucleotide exchange with cytosolic pools. A protein that stimulates the rate of exchange of guanine nucleotide on p21w has been identified and characterized in cytoplasmic extracts of human placenta. The exchange-promoting protein runs on a gel filt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
1

Year Published

1991
1991
2000
2000

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(56 citation statements)
references
References 17 publications
3
52
0
1
Order By: Relevance
“…In the case of ras p21, GTPase-activating protein (GAP) interacts with p21-GTP and enhances the GTPase activity of ras p21 (34,35). Stimulators of the dissociation of the ras p2l-GDP complex have also been reported (36)(37)(38)(39). However, no evidence showing that these factors are responsible for altering the GDP/GTP state of ras p21 in response to exogenous stimuli has been presented.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of ras p21, GTPase-activating protein (GAP) interacts with p21-GTP and enhances the GTPase activity of ras p21 (34,35). Stimulators of the dissociation of the ras p2l-GDP complex have also been reported (36)(37)(38)(39). However, no evidence showing that these factors are responsible for altering the GDP/GTP state of ras p21 in response to exogenous stimuli has been presented.…”
Section: Resultsmentioning
confidence: 99%
“…They hydrolyze GTP to GDP, and the rate of hydrolysis is regulated by GTPase activating proteins or GAPs (37). Stimulation of guanine nucleotide exchange, induced by Ras exchange factors (38), will lead to GTP loading and activation of Ras. Activation of Ras can thus be accomplished either by inhibiting GAPs or stimulating exchange factors.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a number of proteins have been identified that are implicated in direct interactions with p21tm' in yeast and in mammals (2,11). In mammals, the proteins interacting with p21tm' may be placed into two groups: those that potentiate the GTPase activity of p21tm5, such as GTPase-activating protein (GAP) and the locus involved in hereditary neurofibromatosis (NF-1) (12)(13)(14) and those that catalyze GTP/GDP exchange by p21tm' (15)(16)(17)(18). Nevertheless, their role in the ras pathway is still unclear (2,9,19).…”
Section: Introductionmentioning
confidence: 99%